Promoting Inclusion in Your Practice for Transgender and Gender Non-Conforming Clients: Utilizing the Inclusive Financial Well-being Empowerment Model - Goldie Prelogar-Hernandez; Megan A McCoy; Meghaan Lurtz; Kenneth J White (Journal of Financial Therapy, 2022)
Despite increasing attention to cultural humility and inclusivity for financial therapy, mental health, and financial practitioners, little is written about the best practices for working with transgender and gender non-conforming (GNC) clients. This theoretical paper will review these best practices and will present a hypothetical financial therapy case study that utilizes the Inclusive Financial Well-being Empowerment Model (IFWEM). The goal of this work is to introduce practitioners to the best practices for working with transgender and GNC clients in an inclusive and empowering way and to promote future data-driven research for this population.
Keywords: transgender; gender non-conforming; Inclusive Financial Well-being Empowerment Model